Modulation of leucocytic angiotensin-converting enzymes expression in patients maintained on high-permeable haemodialysis. Issue 1 (19th July 2017) - Trojanowicz, Bogusz; Ulrich, Christof; Fiedler, Roman; Martus, Peter; Storr, Markus; Boehler, Torsten; Werner, Kristin; Hulko, Michael; Zickler, Daniel; Willy, Kevin; Schindler, Ralf; Girndt, Matthias
Abstract: Background: High mortality of haemodialysis patients is associated with systemic chronic inflammation and overactivation of the renin–angiotensin system (RAS). Insufficient elimination of pro-inflammatory immune mediators, especially in the molecular weight range of 15–45 kDa, may be one of the reasons for this. Employment of haemodialysis membranes with increased permeability was shown to ameliorate the inflammatory response and might modulate the effects of local RAS. In this study, we tested the impact of high cut-off (HCO), medium cut-off (MCO) and high-flux (HF) dialysis on leucocytic transcripts of angiotensin-converting enzymes (ACE and ACE2). Additionally, the impact of HCO, MCO and HF sera and dialysates on local ACEs and inflammation markers was tested in THP-1 monocytes. Methods: Patients' leucocytes were obtained from our recent clinical studies comparing HCO and MCO dialysers with HF. The cells were subjected to quantitaive polymerase chain reaction (qPCR) analyses with TaqMan probes specific for ACE, ACE2 and angiotensin II (AngII) and Ang1–7 receptors. Sera and dialysates from the clinical trials as well as samples from in vitro dialysis were tested on THP-1 monocytic cells. The cells were subjected to qPCR analyses with TaqMan probes specific for ACE, ACE2, interleukin-6 and tumour necrosis factor α and immunocytochemistry with ACE and ACE2 antibodies. Results: Leucocytes obtained from patients treated with HCO or MCO demonstrated decreased transcript expression of ACE, while ACE2 was significantly upregulated as compared with HF. Receptors for AngII and Ang1–7 remained unchanged. THP-1 monocytes preconditioned with HCO and MCO patients' or in vitro dialysis sera reflected the same expressional regulation of ACE and ACE2 as those observed in HCO and MCO leucocytes. As a complementary finding, treatment with HCO and MCO in vitro dialysates induced a pro-inflammatory response of the cells as demonstrated by elevated messenger RNA expression of tumour necrosis factor α and interleukin-6, as well as upregulation of ACE and decreased levels of ACE2. Conclusions: Taken together, these data demonstrate that employment of membranes with high permeability eliminates a spectrum of mediators from circulation that affect the RAS components in leucocytes, especially ACE/ACE2.